Accounts Receivable Management Practices and Financial Performance of Manufacturing Companies in Rwanda; A Case Study of CIMERWA Plc - Mbarushimana, Emmanuel; Kengere, Osiemo (Journal of Finance and Accounting, 2023)
The general objective of this study was to determine the effects of accounts receivable management practices on financial performance of manufacturing companies in Rwanda. The specific objectives were to: analyze the effect of Credit policy on financial performance of manufacturing companies in Rwanda, examine the effect of Collection policy on financial performance of manufacturing companies in Rwanda, establish the effect of Credit analysis on financial performance of manufacturing companies in Rwanda and assess the effect of Billing and invoicing on financial performance of manufacturing companies in Rwanda. The study adopted a descriptive cross-sectional survey research design which allowed the collection of primary quantitative data through structured questionnaires. The target population was 61 employees from Cimerwa Plc. Census approach was used in this study. Both primary and secondary data was used for the study. Primary data was collected using a well-structured questionnaire. The study utilized questionnaires as an instrument for data collection. Data was analyzed for descriptive and inferential statistics using SPSS version 21. Descriptive statistics such as mean, standard deviation was used to test the data. Ordinary Least Square method was utilized to establish the cause-effect relationship between variables while hypotheses were tested at 5% significance level. The findings reveal that Credit Policy and Credit Analysis have a statistically significant positive impact on Financial Performance (B = 0.502, Beta = 0.274, p = 0.033 and B = 0.595, Beta = 0.548, p = 0.004, respectively), suggesting that a more favorable credit policy and more robust credit analysis positively affect financial performance. In contrast, the results suggest that Collection Policy and Billing and Invoicing do not have a significant influence on Financial Performance (B = -0.007, Beta = -0.008, p = 0.942 and B = -0.377, Beta = -0.327, p = 0.069, respectively). This study in Rwanda emphasizes the significant impact of effective accounts receivable management on manufacturing companies’ financial performance. It advocates for prudent credit policies, streamlined billing processes, and comprehensive credit analysis to enhance liquidity, profitability, and overall financial health. The recommendation for CIMERWA PLC includes implementing efficient credit policies and collection procedures for improved financial outcomes. Future research addressing Rwanda’s specific economic context is suggested for tailored insights. Keywords: Accounts Receivable Management Practices, Financial Performance, Manufacturing Companies, Cimerwa Plc, Rwanda